Image quality and diagnostic accuracy of non-invasive coronary imaging with 16 detector slice spiral computed tomography with 188 ms temporal resolution. Issue 7 (14th June 2005) - Kuettner, A; Beck, T; Drosch, T; Kettering, K; Heuschmid, M; Burgstahler, C; Claussen, C D; Kopp, A F; Schroeder, S
Abstract : Objective: To evaluate image quality and clinical accuracy in detecting coronary artery lesions with a new multidetector spiral computed tomography (MDCT) generation with 16 detector slices and a temporal resolution of 188 ms. Methods: 124 consecutive patients scheduled for invasive coronary angiography (ICA) were additionally studied by MDCT (Sensation 16 Speed 4D). MDCTs were analysed with regard to image quality and presence of coronary artery lesions. The results were compared with ICA. Results: 120 of 124 scans were successful. The image quality of all remaining 120 scans was sufficient (mean (SD) heart rate 64.2 (9.8) beats/min, range 43–95). The mean calcium mass was 167 (223) mg (range 0–1038). Thirteen coronary segments were evaluated for each patient (1560 segments in total). Image quality was graded as follows: excellent, 422 (27.1%) segments; good, 540 (34.6%) segments; moderate, 277 (17.7%) segments; heavily calcified, 215 (13.8%) segments; and blurred, 106 (6.8%) segments. ICA detected 359 lesions with a diameter stenosis > 50% and MDCT detected 304 of 359 (85%). Sensitivity, specificity, and positive and negative predictive values were 85%, 98%, 91%, and 96%, respectively. The correct clinical diagnosis (presence or absence of at least one stenosis > 50%) was obtained for 110 of 120 (92%) patients. Conclusions: MDCT image quality can be further improved with 16 slices and faster gantry rotation time. These results in an unselected population underline the potential of MDCT to become a non-invasive diagnostic alternative, especially for the exclusion of coronary artery disease, in the near future.